Profissionalização dos professores: (Re)posicionamento nas classificações das profissões - Joana Campos (Universidade do Minho, 2016)
The education and training of the population is n owadays an impo rtant task. Political decision is not made without measuring ed ucational outcomes (Schleicher, 2012). Therefore, the re is an increasing demand in what teacher performance is con cerned (Lanthaum e, 2006 ; Schleicher, 2012). The text is part of a wider study on teache rs in the Portuguese e ducational system. In the analysis made, the available knowledge on the p roc es s of teacher professionalization in Portugal was enhanced. The analysis of teachers' pr ofessional group h as been d eveloped in conne ct io n with its pr ofessionalization process, in pa rticular the question s around the differentiation pro cesses and internal homogenization, focusing the analysis on the (re)placement of teachers in the cla ssification of professio ns. Methodologically, th e basic sources for the descrip tors of groups of classifications of professions are the ones expr essed in intern ational and national classifications.